Disrupting Institutional Models of Writing - Tracy, Dale (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2022)
To invite more than imitation, institutional models—of writing and beyond—must leave space for individuals to bring their specific creative intelligence to bear on the rhetorical context. This reciprocal use of models depends on preparing for all students but also on having an open stance to the individual students not adequately accounted for in those preparations, an open stance through which the presence of actual students can disrupt harmful or limited models. Adopting new tools and practices is one thing; adopting a new stance with which to find, approach, understand, and use new tools and practices is something else—something more difficult to bring into public discussion and explicit consideration. I use the practice of book recommendation as an example through which to consider this knowing on the go.